Unveiling heterogeneity among batik SMEs: A knowledge management and financial performance perspective - Fandi Achmad; Sinta Aryani; Iwan Inrawan Wiratmadja; Shuhaida Mohamed Shuhidan (Universitas Sultan Ageng Tirtayasa, 2026)
Batik Small and Medium Enterprises (SMEs) play a vital role in local economic development and cultural preservation. However, Batik SMEs often face persistent challenges related to uneven knowledge management practices and unstable financial performance, which limit their sustainability. Existing studies tend to treat SMEs as a homogeneous group, overlooking internal differences in organizational capabilities and financial outcomes. This study aims to unveil the heterogeneity among Batik SMEs by mapping their profiles based on knowledge management and financial performance using a clustering approach. A quantitative research design was employed, with data collected from Batik SMEs in Rembang Regency through structured questionnaires administered to owners or managers. Knowledge management was measured across four dimensions: knowledge creation, acquisition, sharing, and application, while financial performance was assessed using indicators of profitability, revenue growth, and investment efficiency. The data were standardized and analyzed using k-means clustering, with the optimal number of clusters determined through the elbow method and silhouette coefficient. The results reveal two distinct clusters. The first cluster represents knowledge-driven and financially resilient Batik SMEs with strong knowledge management capabilities and superior financial performance. The second cluster consists of resource-constrained and knowledge-lagging SMEs characterized by weak knowledge utilization and lower financial outcomes. These findings highlight the critical role of knowledge management in shaping financial performance and emphasize the need for differentiated managerial strategies and policy interventions to enhance the sustainability of Batik SMEs.